1999
DOI: 10.1177/019262339902700410
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Severe Nephropathy and Pheochromocytoma in the Male F344 Rat— The National Toxicology Program Experience

Abstract: The possible correlation between the severity of chronic progressive glomerulonephropathy (CPN) and the incidence of adrenal pheochromocytoma was examined in selected studies of male Fischer 344 (F344) rats at the National Toxicology Program (NTP). The NTP historical control database was first examined in order to determine whether there was association between the severity of CPN and the occurrence of adrenal pheochromocytoma in unexposed animals. Following this analysis, the 125 most recent NTP studies cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…food intake), body weight [16][17][18][19][20][21] , housing 22,23 and certain kinds of morbidity such as CPN 24 . In regard to the studies included in the present survey, there were no differences in diet composition or housing conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…food intake), body weight [16][17][18][19][20][21] , housing 22,23 and certain kinds of morbidity such as CPN 24 . In regard to the studies included in the present survey, there were no differences in diet composition or housing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors, including diet [5][6][7][8][9][10][11][12][13][14][15] , body weight [16][17][18][19][20][21] , housing 22,23 and certain kinds of morbidity such as chronic progressive nephropathy (CPN) 24 , influence the occurrence of tumors. Nyska et al 24 suggested that there may be a positive correlation between the severity of CPN and the incidence of pheochromocytomas in Fischer 344 rats.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nyska et al (21) suggested that increased severity of nephropathy may be associated with disturbed calcium and phosphorous homeostasis, secondary hyperparathyroidism leading to hypercalcemia (3). Perturbation in calcium homeostasis was documented to be associated with increased chromaffin cell proliferation and pheochromocytoma (13,39,40).…”
Section: Tumor Incidence Datamentioning
confidence: 99%